Planar on-chip micro-supercapacitors based on graphene by chemical vapor deposition. (4th July 2019) - Zhang, Guangyu; Liu, Jiabao
Abstract: Micro-supercapacitors (MSCs) are becoming one of the research frontiers in the field of chip storage devices. Here ultrahigh scanning rate, narrowing, planar interdigital graphene-based MSCs were fabricated by chemical vapor deposition (CVD) and photolithographic micro-fabrication. The energy density was up to 34.48 mWh cm −3 because of the interdigital architecture and monolayer graphene electrode. In addition, capacitance retention rates remained over 93.80% after 2500 charge/discharge cycles, which showed graphene-based MSCs good stability. More importantly, the MSCs can be operated well at an ultrahigh scan rate of up to 5000 V s −1 . This paper provides an important reference for chip storage devices.